Digital transformation and organizational knowledge: A systematic literature review - Rita de Cássia Arantes (Universidade Federal do Ceará, 2021)
Literature has pointed out that Digital Transformation (DT) is imposing a complete organizational change on companies. However, there is still a limited understanding of the changes related to knowledge and its processes in this scenario. Therefore, the objective was to verify how the field of study of knowledge management is developing in light of the changes caused by DT. The study used three databases to collect articles, and the data were analyzed with VOSviewer and content analysis. The results indicate that companies must develop new resources and capabilities (common and dynamic) to take advantage of DT opportunities. The study contributes to a better understanding of knowledge as a strategic resource in DT.